Study on the multidrug resistance and transmission factors of Staphylococcus aureus at the ‘animal–environment–human’ interface in the broiler feeding cycle - Hu, Fangyuan; Liu, Yaopeng; Wang, Lin; Wang, Juan; Liu, Na; Li, Yan; Duan, Xiaoxiao; Wang, Junwei; Lu, Mingzhe; Liu, Junhui; Qu, Zhina; Han, Keguang (Frontiers in Microbiology, 2025)
Multidrug-resistant Staphylococcus aureus (S. aureus) poses an increasingly serious threat to agricultural safety and public health. Based on the concept of “One Health,” this study analyzed the multidrug resistance and transmission factors of S. aureus isolated from the “animal–environment–human” interface during one feeding cycle of commercial broilers in China by using antimicrobial susceptibility testing and whole genome sequencing (WGS) technologies. The results showed that in stage 1, the isolation rate of S. aureus was 1.32% (6/453), that of workers was 25.0% (4/16), and that of environmental samples was 0.69% (2/287), and the multidrug resistance rate was 83.33%. After one feeding cycle, the isolation rate of S. aureus (221/772, 28.63%) increased significantly (p < 0.01) during stage 2, and the multidrug resistance rate was as high as 97%. The resistance rates to eight drugs including erythromycin, clindamycin, enrofloxacin, ofloxacin, doxycycline, florfenicol, tylosin, and tilmicosin were elevated, but the differences were not significant (p > 0.05). ST398 (79.13%) was the dominant strain in both stages, which was prevalent in 11 types of samples from 3 sources and clustered in the same sub-branch of the single-nucleotide polymorphism (SNP) evolutionary tree. The loci difference between the strains ranged from 1 to 541, with SNPs of less than 10 between the human strains of stage 1 and the three sources in stage 2. The 42 representative strains carried mobile elements, mainly plasmid replicons (10 types), transposons (3 types), and 20 antibiotic resistance genes in 9 classes. A total of 10 ST398 strains exhibited the fosB gene for fosfomycin resistance, and 6 ST9 strains from stage 2 exhibited the mecA resistance gene. The SNP evolutionary analysis revealed that the fosB resistance gene might have been brought in by workers during stage 1. This study revealed the critical impact of environmental residual and worker-carried S. aureus, as well as the transmission of antibiotic resistance in stage 1. It highlighted the importance of the “One Health” approach and biosecurity measures and provided recommendations for the prevention of the spread of pathogens and resistance.